2005
DOI: 10.1103/physrevb.72.085418
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution angle-resolved photoemission investigation of the electronic structure of Cr-intercalated1TTiTe2

Abstract: We report the results of the study by angle-resolved photoelectron spectroscopy of intercalated compound Cr 1/3 TiTe 2 . In the range of binding energies up to 6 eV we obtained band mapping along ⌫ -M, ⌫ -MЈ, and M -K directions of the Brillouin zone. It was established that electronic structure of TiTe 2 changes substantially under the inclusion of Cr. An additional, essentially dispersionless band appears at ϳ1 eV below the Fermi level. Band structure calculations allow one to interpret this band as being du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…For both of them, two valence bands are not fully occupied, leading to two hole Fermi pockets around the Γ − A path, and one conduction band is partially occupied, leading to one electron Fermi pocket around the L point. Such semi-metallic characteristics agree well with many ARPES observations [44][45][46], which confirm the validity of our calculation method. The orbital projections illustrate that the valance bands are mostly contributed by the p orbitals (p x &p y ) of the chalcogen atoms, while the conduction bands are mostly from the d orbitals (d z 2 around L point) of Ti atoms.…”
supporting
confidence: 91%
“…For both of them, two valence bands are not fully occupied, leading to two hole Fermi pockets around the Γ − A path, and one conduction band is partially occupied, leading to one electron Fermi pocket around the L point. Such semi-metallic characteristics agree well with many ARPES observations [44][45][46], which confirm the validity of our calculation method. The orbital projections illustrate that the valance bands are mostly contributed by the p orbitals (p x &p y ) of the chalcogen atoms, while the conduction bands are mostly from the d orbitals (d z 2 around L point) of Ti atoms.…”
supporting
confidence: 91%
“…From a number of studies on chemical bonding in various TM x TiZ 2 compounds it is already known that hybridization of 3d states of an intercalated TM atom and its nearest neighborhood is evidence of the covalent origin [10][11][12] of chemical bonding in the majority of intercalated materials. In brief, the covalence of chemical bonding in TM x TiZ 2 results in the compression of the lattice in the c direction shifting the tri-layers closer to each other along a normal line to a basal plane [13], decrease of the conductivity [10], formation of narrow and dispersionless bands in the vicinity of the Fermi level [14,15] and a shift of the Fermi level [16] relative to the energy position of the original TiSe 2 band. Suppression of the magnetic moments of intercalated TM atoms [17] is due to the variation of the localization degree of the TM 3d, Ti 3d electrons and the hybridization of these with the Z element's 4p states.…”
Section: Introductionmentioning
confidence: 99%
“…The question about the difference in the distribution of Cr atoms in the isostructural hosts TiCh 2 and ZrCh 2 (Ch = Se, Te) naturally arises. Concerning the octa-position, it has been found that the chemical bonding in M x TiCh 2 between the M intercalated atom and TiCh 2 host lattice is formed via hybridization of the M valence states and the states of the nearest-neighbor atoms, mainly Ti 3 d z 2 . ,,,, The hybrid states form a dispersionless band , below the Fermi level of the host compound. For a given host lattice, the binding energy of this band is directly proportional to the M atom ionization potential in the observed valence state.…”
Section: Discussionmentioning
confidence: 99%
“…Since the electronic configuration of the IV group transition metal dichalcogenides can be written as Ti 4+ Ch 2 2– , it is clear that the valence electrons introduced at the intercalation with the Cr atoms can either transit to the Ti atoms of the host lattice or form the hybrid states with the nearest neighbors. The second scenario is realized in the Cr x TiSe 2 and Cr x TiTe 2 compounds, , where the Cr 3d/Ti 3d hybrid states form. In this case, the Fermi level is located within the hybrid band.…”
Section: Introductionmentioning
confidence: 99%